Leaching characteristics and hazard evaluation of bottom ash generated from common biomedical waste incinerators. Issue 10 (11th October 2021) - Ramesh Kumar, A.; Vaidya, Atul Narayan; Singh, Ishan; Ambekar, Kajal; Gurjar, Suyog; Prajapati, Archana; Kanade, Gajanan Sitaramji; Hippargi, Girivyankatesh; Kale, Ganesh; Bodkhe, Sandeep
Abstract: India has more than 202 biomedical waste incinerators, however, knowledge on the chemical characteristics of incinerator ash is lacking. The objective of this study was to evaluate the lecahablility characteristics of bottom ash and to study the levels of incineration by-products viz. polycyclic aromatic hydrocarbons (PAHs), and polychlorinated biphenyls (PCBs). Bottom ash samples from 13 common biomedical waste treatment facilities (CBMWTF) were colleted and subjected to leachig test, sequential extraction procedure (SEP) and PAHs and PCBs analysis. Among metals, cadmium, chromium, manganese, lead and zinc were found higher than the regulatory limits indicating its hazardous nature. SEP showed that substantial fraction of Cd (30%) and Zn (25%) were associated with leachable fractions, whereas metals such as Cr, Fe, Mn, and Ni were mainly associated with reducible, organics and residual fractions. Concentrations of USEPA 16 priority PAHs ranged between 0.17–12.67 mg kg −1 and the total toxic equivalents (TEQ) were in the range of 0.9–421.9 ng TEQ/g. PAHs with 4-rings dominated all the samples and accounted for 68% to total PAHs concentrations. Concentration of Σ19 PCB congeners ranged from 420.4 to 724.3 µg kg −1 . PCBs homologue pattern was dominated by mono- to tetra chlorinated congeners (60–86%). The findings indicate the need for segregation of plastics from biomedical waste, improvement of combustion efficiency, and efficient air pollution control devices for the existing incinerators in CBMWTFs.